2018
DOI: 10.1371/journal.pbio.2005127
|View full text |Cite
|
Sign up to set email alerts
|

Neural responses to natural and model-matched stimuli reveal distinct computations in primary and nonprimary auditory cortex

Abstract: A central goal of sensory neuroscience is to construct models that can explain neural responses to natural stimuli. As a consequence, sensory models are often tested by comparing neural responses to natural stimuli with model responses to those stimuli. One challenge is that distinct model features are often correlated across natural stimuli, and thus model features can predict neural responses even if they do not in fact drive them. Here, we propose a simple alternative for testing a sensory model: we synthes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
163
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(176 citation statements)
references
References 96 publications
(175 reference statements)
11
163
2
Order By: Relevance
“…The crucial question of whether there is something special in the cortical processing of speech has often been approached through careful acoustic matching of linguistic and nonlinguistic stimuli and comparison of their activation patterns in the brain [9][10][11]. The meticulous use of acoustically modified sounds has shown that while primary auditory cortices respond identically to speech and acoustically matched non-speech sounds, responses in nonprimary regions differ [9,12]. However, natural, meaningful and behaviorally relevant sounds might more accurately capture the cortical sensitivity to the most relevant spectrotemporal features for sound processing [13].…”
Section: Introductionmentioning
confidence: 99%
“…The crucial question of whether there is something special in the cortical processing of speech has often been approached through careful acoustic matching of linguistic and nonlinguistic stimuli and comparison of their activation patterns in the brain [9][10][11]. The meticulous use of acoustically modified sounds has shown that while primary auditory cortices respond identically to speech and acoustically matched non-speech sounds, responses in nonprimary regions differ [9,12]. However, natural, meaningful and behaviorally relevant sounds might more accurately capture the cortical sensitivity to the most relevant spectrotemporal features for sound processing [13].…”
Section: Introductionmentioning
confidence: 99%
“…Since there is no one-to-one correspondence between an optimal decision policy and its underlying BDT elements (likelihood, prior, and cost function), it is possible to design Bayesian metamers that involve different prior-cost pairs but are associated with the same optimal policy. This approach parallels fruitful uses of metamers in perception [37][38][39] and machine learning 52 . The key idea is that an observer whose decisions rely on a model-free optimal policy should 'see' the pairs as metamers because they correspond to the same policy.…”
Section: Discussionmentioning
confidence: 89%
“…More generally, in decision-making tasks, there are usually numerous pairs of priors and cost functions that, when combined, could lead to indistinguishable decision policies ( Figure 1b). Analogous to the notion of metamers in perception [37][38][39] , we will refer to such pairs of priors and cost functions as prior-cost metamers. Because of the existence of such metamers, it remains an important and unresolved question whether decisions are made based on independently learned priors and cost functions.…”
Section: Introductionmentioning
confidence: 99%
“…While our stimulus set was designed to minimize confounds between these models (see Methods), we would not necessarily expect a given set of fMRI voxels or MEG sensor patterns to correlate only with one and not the other, both due to the intrinsic correlation between sound acoustics and categories (Theunissen and Elie, 2014) and the fact that neurons throughout primary and nonprimary auditory cortex are responsive to low-and higher-level sound properties (King and Nelken, 2009;Norman-Haignere and McDermott, 2018;Staeren et al, 2009) However, in a hierarchical processing stream, we would expect their respective contributions to vary systematically between regions over time. Thus, we computed the difference between Category and Cochleagram model correlations (Fisher-z normalized to enable direct comparison) with MEG and fMRI patterns.…”
Section: Systematic Trend From Acoustic To Semantically Dominated Camentioning
confidence: 99%
“…We therefore assigned ranks based on independent spatial (functional anatomy) and temporal (fusion-derived peak latency) criteria. For the spatial analysis, we first differentiated primary auditory cortex based on convergent anatomical, histological and functional criteria (Morosan et al, 2001;Norman-Haignere and McDermott, 2018;Sweet et al, 2005), then ranked non-primary areas progressing along and beyond the supratemporal plane. We assigned PAC a rank of 1; TE1.2, PP, and PT (all adjacent to PAC) a rank of 2; TVAx (farther along the posterolateral STG) a rank of 3; LIFG a rank of 4; and FFA, PPA, MPA and LOC a rank of 5.…”
Section: Systematic Trend From Acoustic To Semantically Dominated Camentioning
confidence: 99%